“A Group of Fellow Travellers Who Understand”: Interviews With Autistic People About Post-diagnostic Peer Support in Adulthood - Crompton, Catherine J.; Hallett, Sonny; McAuliffe, Christine; Stanfield, Andrew C.; Fletcher-Watson, Sue (Frontiers in Psychology, 2022)
Receiving a diagnosis of autism in adulthood can be a life changing event, impacting identity, relationships, and mental health. A lack of post-diagnostic support has been highlighted by autistic adults, their allies, clinicians, and service providers. It can be a source of distress for autistic adults, reinforcing feelings of social isolation and rejection. Peer support could be a cost-effective, flexible, and sustainable model to provide community-based support for autistic adults. However, there is little research on the value of peer support, despite calls from the autistic community. This qualitative study explored autistic experiences and needs post-diagnosis, identifying specific ways that peer support may benefit them, and exploring the limitations of peer support. Twelve autistic adults who had all received an autism diagnosis in adulthood completed a semi-structured interview focusing on the diagnostic experience, post-diagnostic support needed and provided, engagement with the autistic community, and post-diagnostic peer support. Thematic analysis of interview transcripts resulted in four themes: (1) Mismatch in support needed and provided; (2) Community connection; (3) Flexible and personalised support; and (4) Sustainability. Participants indicated that peer support may be a useful mechanism to support autistic adults’ post-diagnosis and offers unique opportunities not available through other support channels. Though informal peer support exists, it could be more sustainable and effective if well-supported and funded.